1999
DOI: 10.1086/514315
|View full text |Cite
|
Sign up to set email alerts
|

Organization of Patient Care during the Ebola Hemorrhagic Fever Epidemic in Kikwit, Democratic Republic of the Congo, 1995

Abstract: In contrast with procedures in previous Ebola outbreaks, patient care during the 1995 outbreak in Kikwit, Democratic Republic of the Congo, was centralized for a large number of patients. On 4 May, before the diagnosis of Ebola hemorrhagic fever (EHF) was confirmed by the Centers for Disease Control and Prevention, an isolation ward was created at Kikwit General Hospital. On 11 May, an international scientific and technical committee established as a priority the improvement of hygienic conditions in the hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
94
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(95 citation statements)
references
References 9 publications
1
94
0
Order By: Relevance
“…Only a few EVD cases after needle sticks have been reported [46,53,[56][57][58][59][60][61][62][63][64][65]. However, parenteral inoculation is clearly established as a potent means of transmission and was associated with a shorter incubation period (6.3 days vs 9.5 days) and a higher overall mortality level (100% vs 88%) during the initial outbreak of EVD, in Yambuku during 1976 [66].…”
Section: Contact With Body Fluids and Cadaversmentioning
confidence: 99%
“…Only a few EVD cases after needle sticks have been reported [46,53,[56][57][58][59][60][61][62][63][64][65]. However, parenteral inoculation is clearly established as a potent means of transmission and was associated with a shorter incubation period (6.3 days vs 9.5 days) and a higher overall mortality level (100% vs 88%) during the initial outbreak of EVD, in Yambuku during 1976 [66].…”
Section: Contact With Body Fluids and Cadaversmentioning
confidence: 99%
“…The health care system in DRC was impaired. Guimard et al (1999) reported that during the outbreak at the Kikwit hospital, "The hygienic working conditions were far from ideal" (p. 269). There was no running water, no electricity, and no working waste disposal system.…”
Section: Lack Of Resources and Political Economymentioning
confidence: 99%
“…Ill patients have a very high viremia, and RT-PCR has been shown to be useful in an epidemic setting (Leroy et al, 2000 ;Sanchez et al, 1999). It is also routinely used on shipped specimen in specialized laboratories (Guimard et al, 1999).…”
Section: Introductionmentioning
confidence: 99%